Fungsi Musik Gala Di Kelurahan Tubo Kota Ternate Provinsi Maluku Utara - Imitha Muslimah Chaerani; R.A.D Sri Hartati; Sri Sunarmi (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
The research entitled Functions of Gala Music in Tubo Village, Ternate City, North Maluku Province aims to discover how Gala music functions in Tubo Village, North Maluku Province. Along with the times, Gala Music in Ternate is no longer played for ritual activities, for example, wedding ceremonies, circumcisions, or picking up guests, but only for performances as public entertainment. Habits and traditions began to shift with the advent of modern music so that slowly the old customs or rituals rarely involved Gala music anymore. The theory used as a reference in this study is the Function Theory and the Sociology of Art approach. The research method used is a descriptive qualitative method using data collection techniques such as observation, interviews, documentation and literature studies with the acquisition of data encountered both directly and indirectly understood and evaluated. The existence of gala music continues to grow in the current generation. The results showed that the function of Gala music in the Tubo Village was a function of emotional expression, a function of appreciating aesthetics, entertainment function, communication function, symbolic function, a function of physical response and bodily reaction, a function of validating social institutions, a function related to social norms, a function of continuity of culture and function of integrating society. With the existing developments, Gala music is played in collaboration with the music of Togal, Lala and several other traditional musics. This indicates that Gala music is present to meet the community's cultural needs so that it greatly influences cultural stability in the City of Ternate, especially in the Tubo Village.